THE EFFECTIVENESS OF THE KUMON METHOD WITH TAPERTIC MEDIA ON STUDENTS' UNDERSTANDING OF THE MULTIPLE CONCEPT OF AN-NAJAH TAKENGON INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Hilliyani Hilliyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
This study aims to determine the effectiveness of the Kumon method with tapertis media in understanding the concept of mathematical multiplication. The use of tapertis media aims to make learning more interesting and students can easily accept lessons at school. This study uses a quantitative approach to the type of experimental research. This research was conducted at SD IT An-Najah, Central Aceh District. The population in this study were all students of SD IT An-Najah. The research sample was the fourth grade students of SD IT An-Najah. The results showed that: There was a difference in the average pretest score of the experimental class which was higher than the control class (51.91 > 48.17). There is a difference in the average posttest score for the experimental class which is also higher than the control class (80.64 > 75.52). In addition, the n-gain test results for the experimental class were greater than the control class (0.507 > 0.425). The results of the t test also show that the average of the experimental class is higher than that of the control class (80.64 > 72.52). The results of the t test also showed a significance level of <0.05, namely 0.000 <0.05 and 0.001 <0.05. So it can be concluded that the Kumon method with tapertis media is effective in increasing students' understanding of the multiplication concept at SD IT An-Najah.